2020
DOI: 10.1002/anr3.12049
|View full text |Cite
|
Sign up to set email alerts
|

Acute recurrent bradycardia with evoked potential loss during transforaminal lumbar interbody fusion

Abstract: During a transforaminal lumbar interbody fusion a patient experienced acute intermittent bradycardia with manipulation of the intervertebral body space, followed by loss of somatosensory evoked potentials that did not recover. Postoperative evaluation revealed new bilateral lower extremity sensory and motor deficits. We postulate an afferent reflex arc to explain this and other reported instances of bradycardia and asystole during transforaminal lumbar interbody fusion surgery. Awareness of the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The number of spinal surgeries each year is increasing rapidly, and surgeons are constantly looking for new ways to reduce costs and potential surgical complications, particularly iatrogenic spinal injuries [ 9 ]. Spinal cord iatrogenic injuries that occur during instrument manipulation are a major concern for the spine and spinal surgeons, and the need for intraoperative monitoring to assess spinal cord functional integrity becomes even more important as innovative devices are increasingly used in spinal surgery [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of spinal surgeries each year is increasing rapidly, and surgeons are constantly looking for new ways to reduce costs and potential surgical complications, particularly iatrogenic spinal injuries [ 9 ]. Spinal cord iatrogenic injuries that occur during instrument manipulation are a major concern for the spine and spinal surgeons, and the need for intraoperative monitoring to assess spinal cord functional integrity becomes even more important as innovative devices are increasingly used in spinal surgery [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies revealed that hypotension intraoperatively can increase the likelihood of neurologic deficits by reducing spinal cord perfusion pressure (Joshua Yang et al, 2018;CoreyWalker and Park, 2020). Schwan et al (2020) reported that evoked potential waveforms can be lost after recurrent bradycardia during spinal surgery. So, bradycardia and hypotension should be avoided strictly during spinal surgeries, according to the latest guidance (Vitale et al, 2014;CoreyWalker and Park, 2020).…”
Section: Effects Of Dexmedetomidine On Cardiovascular Stabilitymentioning
confidence: 99%